A Case of Focal Segmental Glomerulosclerosis Associated with Aplastic Anemia - Park, Chi Young (The Korean Academy of Medical Sciences, 2004)
The pathogenic mechanism of focal segmental glomerulosclerosis (FSGS) and aplastic anemia are associated with immunologic events which lead to glomerular cell injury or hematopoietic cell destruction. We present an extremely rare case of FSGS with aplastic anemia in a 30-yr-old woman. The laboratory examination show-ed hemoglobin 7.2 g/dL, white blood count of 4,200/µl, platelet count 70,900/µl. Proteinuria (2+, 3.6 g/day) and microscopic hematuria were detected in urinalysis. The diagnosis of FSGS and aplastic anemia were confirmed by renal and bone marrow biopsy. She was treated with immunosuppressive therapy of prednisone 60 mg/day orally for 8 weeks and cyclosporine A 15 mg/kg/day orally. She responded with gradually improving her clinical manifestation and increasing peripheral blood cell counts. Prednisone was maintained at the adequate doses with tapering after 8 weeks and cyclosporine was given to achieve trough serum levels of 100-200 ng/mL. At review ten month after diagnosis and initial therapy, the patient was feeling well and her blood cell counts increased to near normal (Hb 9.5 g/dL, Hct 32%, WBC 8,300/µl, platelet 123,000/µl) and renal function maintains stable with normal range proteinuria (0.25 g/day).